Association between human leukocyte antigens and graft-versus-host disease occurrence after allogenic hematopoietic stem cell transplantation - Cardozo, Daniela Máira (2012)
CONTEXT AND OBJECTIVE: Graft-versus-host disease (GVHD) is one of the complications following allogenic stem cell transplantation. This study investigated an association between human leukocyte antigen (HLA) and the occurrence of acute and chronic GVHD in patients who had received stem cell transplantations from HLA-identical siblings. DESIGN AND SETTING: Retrospective study at Hematology and Hemotherapy Center, Universidade Estadual de Campinas (Unicamp). METHODS: The participants were 176 patients whose first transplant was between 1997 and 2009. HLA genotyping was performed serologically and using the polymerase chain reaction with specific primer sequence. RESULTS: Acute GVHD was positively associated with HLA-A10 (P = 0.0007), HLA-A26 (P = 0.002), B55 (P = 0.001), DRB1*15 (P = 0.0211) and DQB1*05 (P = 0.038), while HLA-B16 (P = 0.0333) was more frequent in patients without acute GVHD. Chronic GVHD was positively associated with HLA-A9 (P = 0.01) and A23 (P = 0.0292) and negatively with HLA-A2 (P = 0.0031) and B53 (P = 0.0116). HLA-B35 (P = 0.0373), B49 (P = 0.0155) and B55 (P = 0.0024) were higher in patients with acute GVHD grade 3 or above, than in other patients. In patients with extensive chronic GVHD, HLA-A9 (P = 0.0004), A24 (P = 0.0059) and A26 (P = 0.0411) were higher than in other patients, while HLA-A2 was lower (P = 0.0097). CONCLUSION: This study suggests that HLA can influence the incidence and severity of acute and chronic GVHD. However, a study with a better design and more patients will be needed to confirm these results.